Kepatuhan Pembatasan Cairan dan Diet Rendah Garam (Natrium) pada Pasien GGK yang Menjalani Hemodialisa - Senny Nur Wulan; Etika Emaliyawati (Universitas Faletehan, 2018)
The mostly caused death on chronic renal failure are overhydration and hypercalemia. Therefore, the compliance of patients with chronic renal failure recognized as attempt to decrease mortality rate of it. The aim of this study was to describe compliance of fluid restriction and a low salt (sodium) diet in patients with chronic renal failure undergoing regular hemodialysis at Hospital dr. Hasan Sadikin. This research used descriptive method with cross-sectional approach. The samples of this research were regular hemodialysis patients who were selected by using consecutive sampling technique of 93 people. The research instrument used questionnaire to measure compliance of fluid restriction and low salt (sodium) diet. Analysis used univariate analysis with median values.The analysis result showed that respondents who are compliance to the restriction of fluid were 35 people or 37.6%, while non-compliance is 58 people or 62.4%. Respondent who were comply of a diet low in salt (sodium) were 31 people or 33.3%, while non-compliance is 62 people or 66.7%. This study showed that most of patients with chronic renal failure did not adhere to restrictions of fluid and low-salt diet (sodium). The increasing of frequency education motivation and dietary fluid counseling in each hemodialysis schedule are nessesary.